EFEKTIVITAS TEKNIK CINEMA THERAPY DALAM KONSELING KELOMPOK UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMA - Findy Eka Maulidyah; Muwakhidah Muwakhidah; Findy Eka Maulidyah (Universitas Negeri Malang, 2024)
Abstract: Self-confidence is important for every individual or student, however, based on research so far, many students still show low self-confidence. The aim of this research is to determine the effectiveness of the Cinema Therapy technique in group counseling to increase the self-confidence of students at Hang Tuah 1 High School Surabaya. This research used a one group pre-test post-test design while the research subjects were 6 students who were obtained using a purposive sampling technique. This research uses a self-confidence questionnaire data collection instrument based on Lautser's theory which consists of 5 indicators that meet validity and reliability, with a total validity of 25 and a reliability result of 0.706. In this research, the data analysis technique used is the Wilcoxon test with the help of SPSS for Windows version 24.0. The research results show from statistical tests where Asymp. Sig (2 tailed) has a value of 0.027 because 0.027 is less than 0.05, it can be said that Ha is accepted, this can be seen by comparing the significant score of 0.05..